Pengaruh Kepemimpinan Servant dan Kepemimpinan Transformasional Terhadap Organizational Citizenship Behavior (OCB) - Melva Hermayanty Saragih; Andana Andana; Farland Al Hafiz; Muhammad Alvin Meilando (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2021)
This study aims to examine the effect of Servant Leadership (SL) and Transformational Leadership (TL) on Organizational Citizenship Behavior (OCB) in a private company in Jakarta, Indonesia. The method used is multiple regression analysis, with a sample of 117 respondents. The results showed that Servant Leadership and Transformational Leadership had a significant effect on Organizational Citizenship Behavior. Thus, SL and TL are variables that are important to be applied in the company, especially in terms of increasing employee commitment and emotional attachment to the company organization.